Factors Affecting the Treatment Success of Short-Term Regimen for Drug Resistant Tuberculosis (DR TB) Patients at Dr. Saiful Anwar General Hospital Malang - Fahmi Adhi Prasetya; Yani Jane Sugiri; Teguh Rahayu Sartono; Harun Al Rasyid (Jurnal Respirologi Indonesia, 2022)
Background: Tuberculosis/TB is a major health problem in the world. Indonesia ranks 3rd in TB cases and 7th in drug resistant (DR) TB cases in the world. In 2016, WHO recommended short term (9–11 month) regimen treatment with a success rate of 84% in several Asian and African countries. The purpose of this study was to determine factors that influence the success and failure of treatment using short-term regimen for DR TB patients at Dr. Saiful Anwar General Hospital Malang.Methods: This was an analytic observational study with retrospective cohort design on 85 short-term regimen DR TB patients who started treatment on October 1, 2017 to September 30, 2018 at the DR TB ward of Dr. Saiful Anwar General Hospital Malang. Data analysis used chi square test with alternative fisher exact test and logistic correlation test.Results: Education level had a significant correlation with treatment success (P=0.036; OR=2.746; CI 95%=1.053-7.165) while Pre XDR TB sputum drug susceptibility test had a significant correlation with treatment failure (P=0.037; OR=1.556; CI 95%=1.180-2.050). Based on logistic correlation test, the predictive variables for treatment outcomes were age, education, criteria for suspected DR TB and drug susceptibility test results of pre XDR TB.Conclusion: The level of education affected the success treatment of DR TB short-term regimen. The results of Pre XDR TB sputum drug susceptibility test influenced the failure of DR TB short-term regimen.